Multiply Binomials When Coefficient is One
Multiply Binomials When Coefficient is One - How it Works - Video
Example 1
Example 1:
When we distribute two binomials, one method is use the FOIL method. F is for the first terms in each parenthesis. O is for the second terms in each parenthesis. I is for the second term in the first parenthesis and the first term in the second parenthesis. L is for the second term in the first parenthesis and the second term in the second parenthesis.
For F we multiply the x and x => x2.
For O we multiply the x and 4 => 4x.
For I we multiply the 6 and x => 6x.
For L we multiply the 6 and 4 => 24.
Now we have x2 + 4x + 6x + 24. Let's combine any like times and in this case we have 4x + 6x => 10x.
So our final answer is x2 + 10x + 24.
Example 2
Example 2:
When we distribute two binomials, one method is use the FOIL method. F is for the first terms in each parenthesis. O is for the second terms in each parenthesis. I is for the second term in the first parenthesis and the first term in the second parenthesis. L is for the second term in the first parenthesis and the second term in the second parenthesis.
For F we multiply the x and x => x2.
For O we multiply the x and 5 => 5x.
For I we multiply the -3 and x => -3x.
For L we multiply the -3 and 5 => -15.
Now we have x2 + 5x - 3x - 14. Let's combine any like times and in this case we have 5x - 3x => 2x.
So our final answer is x2 + 2x - 15.
Example 3
Example 3:
When we distribute two binomials, one method is use the FOIL method. F is for the first terms in each parenthesis. O is for the second terms in each parenthesis. I is for the second term in the first parenthesis and the first term in the second parenthesis. L is for the second term in the first parenthesis and the second term in the second parenthesis.
For F we multiply the x and x => x2.
For O we multiply the x and -4 => -4x.
For I we multiply the 2 and x => 2x.
For L we multiply the 2 and -4 => -8.
Now we have x2 - 4x + 2x - 8. Let's combine any like times and in this case we have -4x + 2x => -2x.
So our final answer is x2 - 2x - 8.
Example 4
Example 4:
When we distribute two binomials, one method is use the FOIL method. F is for the first terms in each parenthesis. O is for the second terms in each parenthesis. I is for the second term in the first parenthesis and the first term in the second parenthesis. L is for the second term in the first parenthesis and the second term in the second parenthesis.
For F we multiply the x and x => x2.
For O we multiply the x and -7 => -7x.
For I we multiply the -2 and x => -2x.
For L we multiply the -2 and -7 => -14.
Now we have x2 - 7x - 2x - 14. Let's combine any like times and in this case we have -7x - 2x => -9x.
So our final answer is x2 - 9x - 14.